Estudo de sinais e sintomas da disfunção temporomandibular em crianças brasileiras - Goberna Fernandez, Isadora Martinelli Gonçalves [UNESP] (2018)
Temporomandibular Dysfunctions (TMD) include clinical problems involving the temporomandibular joint (TMJ), facial muscles, and other structures. In children, the epidemiology of TMD have not yet been well established. Thus, the objective of this study was to investigate the prevalence of signs and symptoms of Temporomandibular Dysfunction (TMD) and its association with systemic condition, medical and dental history, and demographic information, in dental records of children aged 3 to 9 years assisted in a preventive clinic of a public university, during 2009-2016. The clinical records of children (n=356) who attended at the Preventive and Sanitary Dentistry Clinic II of São Paulo State University, School of Dentistry of Araraquara were evaluated and the following data were collected: TMD signs and symptoms (response variable, through 8 questions of the Fonseca Anamnestic Index, answered jointly by the children and parents/guardians to the students of the third year of graduation in Dentistry), medical history and systemic condition, deleterious oral habits, oral condition, access to the dentist, oral hygiene and demographic data. The data were analyzed descriptively and through association tests, with a5% significance level. The independent variables with p<0.15 and with at least 5 cases per category were selected for a multiple logistic regression model. The prevalence of at least one TMD sign and/or symptom was 19.9%, with a high frequency of "yes" answers to the questions that addressed: joint noise and ear pain or near it. In multiple logistic regression, older children or those with dry mouth were more likely to have TMD signs and symptoms (p≤0,026). It was concluded that the prevalence of signs and symptoms of TMD reported was 19.9% and was significantly associated with age and the presence of dry mouth.